An electrochemically aminated glassy carbon electrode for simultaneous determination of hydroquinone and catechol. Issue 3 (27th November 2015) - Wang, Xiuyun; Xi, Min; Guo, Mengmeng; Sheng, Fangmeng; Xiao, Guang; Wu, Shuo; Uchiyama, Shunichi; Matsuura, Hiroaki
Abstract : A simple strategy based on the easy modification of GCE by pre-electrolyzing it in ammonium carbamate aqueous solution was employed for the simultaneous determination of HQ and CC. Abstract : In this contribution, a very simple and reliable strategy based on the easy modification of a glassy carbon electrode (GCE) by pre-electrolyzing GCE in ammonium carbamate aqueous solution was employed for the simultaneous determination of hydroquinone (HQ) and catechol (CC). Compared with bare GCE, the incorporation of nitrogen into the GCE surface structure improved the electrocatalytic properties of GCE towards the electro-oxidation of HQ and CC. The nitrogen-introduced GCE (N-GCE) was evaluated for the simultaneous detection of HQ and CC and the linear ranges for HQ and CC were both from 5 to 260 μM. Their detection limits were both evaluated to be 0.2 μM ( S / N = 3). The present method was applied for the determination of HQ and CC in real river water samples with recoveries of 95.0–102.1%. In addition, a possible detection mechanism of HQ and CC was discussed.